2021
DOI: 10.3389/fresc.2021.755963
|View full text |Cite
|
Sign up to set email alerts
|

When Spinal Neuromodulation Meets Sensorimotor Rehabilitation: Lessons Learned From Animal Models to Regain Manual Dexterity After a Spinal Cord Injury

Abstract: Electrical neuromodulation has strongly hit the foundations of spinal cord injury and repair. Clinical and experimental studies have demonstrated the ability to neuromodulate and engage spinal cord circuits to recover volitional motor functions lost after the injury. Although the science and technology behind electrical neuromodulation has attracted much of the attention, it cannot be obviated that electrical stimulation must be applied concomitantly to sensorimotor rehabilitation, and one would be very diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 180 publications
2
4
0
Order By: Relevance
“…We found that although we observed an increase in spinal excitability when applying TSCS, it did not lead to improved performance of the functional balance task. This reinforces a frequently emphasized principle in the literature that functional training is essential for neurophysiological changes to translate into improved function Flores et al (2021); Taube et al (2007); Nahum et al (2013); Kleim and Jones (2008).…”
Section: Introductionsupporting
confidence: 84%
“…We found that although we observed an increase in spinal excitability when applying TSCS, it did not lead to improved performance of the functional balance task. This reinforces a frequently emphasized principle in the literature that functional training is essential for neurophysiological changes to translate into improved function Flores et al (2021); Taube et al (2007); Nahum et al (2013); Kleim and Jones (2008).…”
Section: Introductionsupporting
confidence: 84%
“…Specifically, both ESS and TSS can promote standing and stepping, as well as volitional activation of otherwise paralyzed lower-limb (LL) muscles ( Angeli et al., 2018 ; Gill et al., 2018 ; Grahn et al., 2017 ; Rowald et al., 2022 ; Sayenko et al., 2019 ). These remarkable clinical outcomes demonstrated in LL functions have prompted several experimental trials to determine if spinal stimulation could be used to improve upper-limb (UL) function following SCI ( Flores et al., 2021 ). While some clinical studies administering ESS and TSS have shown success in improving hand grip force ( Freyvert et al., 2018 ; Gad et al., 2018 ; Inanici et al., 2018 ; Lu et al., 2016 ), limited data exist on 1) the effects of spinal stimulation therapy on other UL functions (including shoulder, elbow, and wrist flexion/extension), 2) objective electrophysiology outcomes, and 3) distinction between restorative and compensatory motor improvement following cervical spinal stimulation interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the group of rats that underwent functional reach training improved in the reaching task substantially when compared to the untrained group. In another study, Flores et al ( 2021 ) showed that in the presence of the neuroplasticity boosting effects of Chondroitinase ABC (Mahajan, 2018 ), rats that underwent specific functional rehabilitation demonstrated considerable improvement in the reaching task when compared to rats that received only Chondroitinase. These studies demonstrate that activity-based training can lead to improved functions.…”
Section: Introductionmentioning
confidence: 99%
“…This includes movement, strength, coordination, walking, manual dexterity, and grip strength exercises. The mechanism by which physical training benefits recovery of motor function in SCI is not well understood (Lynskey, 2008 ; Flores et al, 2021 ), however, there are hypotheses in the literature that support activity-based training. Lynskey ( 2008 ) suggests that recovery after activity-based training relies on sensory feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%